Autistic Trait Level and Reaction Time in Older Adults: The Influence of Sex and Task upon Study Outcome. - Norris, Jade Eloise; Tales, Andrea; Badger, Julia R.; Cousins, Alecia L.; Richards, Emma (Autism in Adulthood, 2026)
Background: The present debate regarding what constitutes "cognitively healthy aging" in people with elevated autistic traits is highly relevant to the diagnosis of age-related conditions such as mild cognitive impairment (MCI) and dementia. Behavioral reaction time (RT) is an important component of cognition and everyday functioning, and it is included in diagnostic testing for such conditions. Autism trait level is not typically considered when including participants in aging-related RT research, and therefore requires examination to address whether those with high levels of autistic traits may show differences in terms of their RT performance, as relevant to testing for MCI and dementia. Methods: In the present study, we examined the relationship between RT and levels of autistic traits in 76 community-dwelling older adults (aged 50–78 years). We also investigated whether there were any differences in the relationship between RT and autistic trait level with respect to sex. Results: We found that the relationship between an individual's levels of autistic traits and their RT scores varied depending on the type of task used, and on sex. In particular, for females, higher levels of autistic traits were related to slower RTs on the Trail Making task (Trails A), a task commonly used in clinical practice. Conclusion: Our findings indicate that some aspects of age-related cognitive decline may be steeper for older adults with higher levels of autistic traits, but that the impact may be different depending on sex, with higher trait levels in females being indicative of poorer RT performance. These findings may explain some of the outcome variability typical of previous studies, and have important implications for interpreting tests used for dementia diagnosis, particularly for older adults on the autism spectrum. Community Brief: Why is this an important issue?: Reaction time (RT) refers to the amount of time that passes between when we perceive something and when we respond to it. It is an important part of our thinking and reasoning abilities called cognition, affecting how we function in daily life, and is included in the tests used for diagnosing age-related conditions including mild cognitive impairment (MCI) and dementia. It is important to understand more about the relationship between autistic traits and RT, particularly as we age. What was the purpose of this study?: A person's level of autistic traits are not typically taken into account when reaction time data is collected from the general population. This data is then used to compare an individual's performance with when diagnosing conditions such as MCI and dementia. This means that, for older adults on the autism spectrum, current practice based on such data may be leading to inaccurate interpretation of cognitive ability. What did the researchers do?: The current study recruited 76 people aged between 50 and 78 years, and investigated the relationship between their reaction time and levels of autistic traits on two different tests. We also analysed whether there were differences between males' and females' performances. What were the results of the study?: We found that the relationship between an individual's levels of autistic traits and their reaction time scores vary depending on the type of task used, and on sex. For example, for females, higher levels of autistic traits were related to slower reaction times on one task. What do these findings add to what was already known?: The findings will be important in determining how clinical test results are interpreted, in particular concerning the diagnosis of MCI and dementia in people with higher levels of autistic traits. In addition, this study indicates that reaction time performance may decline to a greater degree for older adults with higher levels of autistic traits, but that this may be more noticeable in females compared to males. What are potential weaknesses in the study?: This study recruited a higher number of females (N = 51) compared to males (N = 25). This may mean that there are limits to the extent to which conclusions can be drawn regarding the differences between sexes. Further research can aim to address these weaknesses by recruiting larger numbers of male and female older adults. How will these findings help autistic adults now or in the future?: Our findings have important implications for how clinicians should interpret the results of tests used for dementia diagnosis, particularly for older adults on the autism spectrum. Future research should aim to determine whether these results can be replicated with different tests of reaction time, and in older people with even higher levels of autistic traits. Finally, it is noted that studies of autistic traits in the general population cannot replace those with diagnosed autistic older adults. Future studies should therefore seek to determine how meaningful such reaction time data are to assessment and diagnosis of MCI and dementia in autistic older adults, and to determine what constitutes 'cognitively normal ageing' for autistic people as they age.